Anthropomorphism or preparedness? Exploring children's God concepts - Barrett, J; Richert, R (Religious Research Association, 2003)
Historically, the development of God concepts in human cognition has been explained anthropomorphically. In other words, for children especially, God is a big, super-human who lives in the sky. Recent empirical research on the development of these concepts may suggest an alternative hypothesis. In this paper, we review this research and outline the "preparedness hypothesis," which suggests that children may be cognitively equipped to understand some properties of God in a non-anthropomorphic way.